“That’s Not Funny Anymore”: Translating Cultural Humor and Its Equivalence in Murder Mystery - Indah Dwi Hardiasmara; Sholikatus Sa'diyah; M. Agus Suriadi; Hilmi Akmal (Journal of Translation, Linguistics and Literature, 2025)
This research aims to examine the translation of cultural humor in Murder Mystery (2019) and Murder Mystery 2 (2023), and to investigate how cultural equivalence is achieved in Indonesian subtitles by applying Raphaelson West’s Cultural Humor and Eugene Nida's Cultural Equivalence Theory. This research employed a qualitative method. Documentation technique is used for data collection, where data was collected from the dialogue and subtitles of both films, focusing on subtitles that contain cultural humor. The findings show that most cultural humor in films undergoes a change in form or loses its comedic effect in Indonesian translation due to cultural differences between the original speakers and the target audience, as well as limitations in subtitle space and time. Furthermore, several translation strategies are used, including literal translation, transference, cultural equivalent, and adaptation. However, not all strategies are able to preserve the comedic effect to the fullest extent. As a result, this research highlights the importance of cultural sensitivity and creativity on the part of translators in producing translations that are accurate in meaning and convey humorous elements to the target audience.